1997
DOI: 10.1007/bf02439341
|View full text |Cite
|
Sign up to set email alerts
|

The nanocrystalline ceria sol-Gel coatings for high temperature applications

Abstract: Abstract. Sol-gel technology was utilized to produce nanocrystalline thin films of CeO2 on substrates with different oxidation resistance at high temperatures. After deposition, the coatings were composed of CeOz crystallites with a size of 5 nm, randomly oriented on all the substrates. The annealing of gel deposited on Pt and Si substrates was accompanied by evaporation of water and other species and followed by growth of crystallites, without formation of any evident texture. Conversely, the annealing of coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Synthesis techniques include solution-based techniques such as coprecipitation [9,10], hydrothermal [11], micro-emulsion [12], sol-gel [13,14], solution combustion, electrochemical methods and solid-based techniques such as mechanochemical method, chemical vapour deposition [15] and sputtering [16]. The present work emphasises the effect of synthesis conditions on the crystallite size, lattice parameter and lattice strain on ceria nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis techniques include solution-based techniques such as coprecipitation [9,10], hydrothermal [11], micro-emulsion [12], sol-gel [13,14], solution combustion, electrochemical methods and solid-based techniques such as mechanochemical method, chemical vapour deposition [15] and sputtering [16]. The present work emphasises the effect of synthesis conditions on the crystallite size, lattice parameter and lattice strain on ceria nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The lanthanum sol-gel coating was performed using a 0.4 mol.l -1 lanthanum hydroxide solution obtained from the precipitation of lanthanum hydroxide in 0.27 mol 28% ammonia. After filtration, the dissolution of the precipitate is obtained in the 69% nitric acid at 60°C [18]. The lanthanum sol-gel coatings are carried out by dipping the specimens during 2 s in the solution.…”
Section: Methodsmentioning
confidence: 99%
“…Two nano-CeO 2 -dispersed Ni 3 Al coatings showed almost no spallation after pre-oxidation, while 5 mm CeO 2 -dispersed Ni 3 Al coatings experience extensive scale damage. Previous studies had suggested that the reactive element effect was linked to the segregation [33,36] or the precipitation [37,38] of the ions of reactive elements (e.g., Y, La, Ce, Hf) at the scale-grain boundaries or the scale/matrix interface. The ability of CeO 2 particles to supply Ce ions is determined by their sizes, and CeO 2 particles larger than 10 nm could not serve as effective sources of Ce ions [36,39].…”
Section: Effect Of Ceomentioning
confidence: 99%